2009
DOI: 10.1111/j.1439-0396.2008.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic effects of potato protein and fish protein in pigs

Abstract: This study was performed to assess the effects of potato protein and fish protein on concentrations of lipids in plasma and lipoproteins and the expression of genes involved in lipid metabolism in pigs used as an animal model. Therefore, 27 young male pigs with an average body weight of 22 kg were fed diets supplemented with protein extracted from potatoes (containing 849 g protein/kg dry matter), Alaska Pollack fillet as a source of fish protein (containing 926 g crude protein/kg dry matter) or casein which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…The greater absorption was accompanied by higher blood levels of triglycerides in pigs fed on PPC than on CAS while the total cholesterol concentration did not differ. These findings are contradictory to the hypolipidaemic effect of potato protein observed in rats (De Schrijver, 1990) and its hypocholesterolaemic but not hypolipidaemic, effect found in pigs (Spielmann et al, 2009). Pigs and not rats, are considered as a better model of lipid metabolism when related to humans.…”
Section: Concentration Of Protein and Lipid Metabolites In Blood (Expcontrasting
confidence: 54%
See 2 more Smart Citations
“…The greater absorption was accompanied by higher blood levels of triglycerides in pigs fed on PPC than on CAS while the total cholesterol concentration did not differ. These findings are contradictory to the hypolipidaemic effect of potato protein observed in rats (De Schrijver, 1990) and its hypocholesterolaemic but not hypolipidaemic, effect found in pigs (Spielmann et al, 2009). Pigs and not rats, are considered as a better model of lipid metabolism when related to humans.…”
Section: Concentration Of Protein and Lipid Metabolites In Blood (Expcontrasting
confidence: 54%
“…The animals fed on cereal diet containing PPC as the only protein source had similar feed intake and growth rate, and even slightly better feed conversion than piglets fed on casein-supplemented diet. Absence of negative effect of potato protein on growth performance of older pigs (initial body weight 22 kg) was found also by Spielmann et al (2009) who fed diets containing casein, fish meal or potato protein at the level increased from 15 to 19.4% during 21 days of experiment. Potato protein appeared to be a good substitute of fish meal when fed at 6% level to piglets of the initial body weight 7.5 kg (Sardi et al, 2005) and when fed at 8% level with faba beans as the protein source for growing-finishing pigs (Sundrum et al, 2000).…”
Section: Concentration Of Protein and Lipid Metabolites In Blood (Expmentioning
confidence: 86%
See 1 more Smart Citation
“…[1][2][3][4][5][6][8][9][10]. It has been hypothesized that effects of these proteins on cholesterol metabolism, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported many times that protein isolated from soybeans has hypocholesterolaemic effects in laboratory animals, pigs and humans when compared to casein [2,[5][6][7] . Recently, it has been found that proteins extracted from sweet lupins [8] and peas [9] as well as from fish as a source of a protein of animal origin [10][11][12] also have beneficial effects on the cholesterol metabolism of rats and pigs.…”
Section: Introductionmentioning
confidence: 99%